RNA binding protein FXR1-miR301a-3p axis contributes to p21(WAF1) degradation in oral cancer - Majumder, Mrinmoyee (PLoS Genet, 2020)
RNA-binding proteins (RBPs) associate with the primary, precursor, and mature microRNAs, which in turn control post-transcriptional gene regulation. Here, by small RNAseq, we show that RBP FXR1 controls the expression of a subset of mature miRNAs, including highly expressed miR301a-3p in oral cancer cells. We also confirm that FXR1 controls the stability of miR301a-3p. Exoribonuclease PNPT1 degrades miR301a-3p in the absence of FXR1 in oral cancer cells, and the degradation is rescued in the FXR1 and PNPT1 co-knockdown cells. In vitro, we show that PNPT1 is unable to bind and degrade the miRNA once the FXR1-miRNA complex forms. Both miR301a-3p and FXR1 cooperatively target the 3'-UTR of p21 mRNA to promote its degradation. Thus, our work illustrates the unique role of FXR1 that is critical for the stability of a subset of mature miRNAs or at least miR301a-3p to target p21 in oral cancer.